Pengalaman Keluarga Mempersiapkan Diri Menghadapi Bahaya Gunung Merapi di Desa Tegalmulyo: Studi Fenomenologi - Nurhidayati, Istianna; Agustina, Nur Wulan; Anggraini, Novia (Universitas Respati Yogyakarta, 2019)
Individual and family represent the main stakeholder in alertness. Family represent tip of lance, subjek and object from alertness, because having an effect on directly to disaster risk. The aim of the research is to get the meaning about the family experience in unlimbering to face the natty mount danger in Tegalmulyo village. This research used qualitative design with the phenomenology approach. This research population is all of family Tegalmulyo village. Sum up the sample research as much 7 participle obtained that used appropriate purposive sampling of criterion of inclusion research. The researcher used indepth interview to collect the data. The result of theme research is eleven themes that are natural disaster on the slopes of Merapi, the signs of Mount Merapi disaster, the danger of Mount Merapi eruption, equipment and equipment, evacuation site, evacuation plan, traditional early warning system, early warning system with modern technology, family empowerment , psychological feelings, evacuation assistance. The conclusion of this research are the experience of family preparedness to disaster in Tegalmulyo village is ready to face the danger of Mount Merapi.